P-19 Our roots, our liverpool, our journey... the benefits of an art project in bereavement group work. Issue Volume 5: Issue (2015)Supplement 3 (1st November 2015) - Pugh, Elaine; Crompton, Christine; Marley, Kate; Harvey, Gillian
Abstract : Woodlands Hospice runs a monthly drop-in bereavement group to provide a sensitive environment for people to share feelings, experiences, gain mutual support, make friends and gain confidence. An art project was proposed to represent the bereavement journey. The group agreed on three themes: Backdrop of the Liverpool sky line Roots from a tree representing, pain, growth and family Personal sentimental items, each piece is unique to that person and tells an individual story that can be shared. Together forming an illustration of genuine understanding of the impact of losing a loved one. Project objectives were to: promote inclusive activity, enabling people to drop in and out at any time use creative therapy as a method of expressing grief use the activity as a way of enhancing group support build resilience and gain ideas for coping strategies work together in a safe, empathic environment complete a project that could be shared and enjoyed by others tell a story that connects people on a personal level and reaches out to other bereaved people to bring comfort and hope. To ensure inclusivity and recognise the diverse nature of loss, grief, culture, beliefs and values, no one person took responsibility for leading the work. Workshops were facilitated by a member of staff and were designed to give support to any group member needing help to deal with heightened emotions and feelings that may have emerged. Results: The completed project is powerful and moving, symbolising a journey that connects people through experiences of loss and grief. The safe environment enabled ease of expression; and the opportunity for people to enjoy a new skill leading to a natural bond and an ease of storytelling. Conclusion: The project provided opportunities for individuals to connect on a social level, reducing isolation and loneliness. It enabled participants to share how they could gain relief from sadness and build confidence to continue with their lives.